Tempo de residência da água em um sistema experimental de aquicultura integrada com camarões, ostras e macroalgas. - Rocha, Nayana Moura da (2009)
Shrimp culture presented at a world-wide level a significant growth in recent years, mainly in tropical and subtropical regions, however, this expansion comes with diverse environment negative impacts, mainly related to the cultures effluents, which are rich in nitrogen and phosphorous, that are many times discarded in the environment without any previous treatment. Aiming the improvement of its techniques the aquaculture industry needs to develop new culture methods, which can improve its efficiency and attenuate the consequences of its activities to keep the health of aquatic ecosystems. In this context appears the integrated aquaculture, witch involves the culture of different organisms in the production process, and can be an ambient and economic viable alternative. In order to study this technology efficiency, the water quality of an integrated aquaculture system with shrimps, oysters and macroalgae was evaluated in laboratory conditions, using three different water residence times. The integrated system was composed of five 50 L aquariums, one for shrimps culture, one destined to ration remaining portions and dejections sedimentation, one for oysters culture, another one for macroalgae culture and a last one to store the recirculation water, which was carried through the system by pumping after 48, 72 and 96 hours of water residence. The physical-chemical parameters temperature, salinity and dissolved oxygen were daily monitored and the concentrations of ammonium, nitrite, nitrate and phosphate, turbidity and pH evaluated weekly. Cultivated organisms growth was also weekly attended and after the end of the experiment, shrimps, oysters and macroalgae total protein content were determined. The results showed that sedimentation reduced nitrite and nitrate concentrations, as well as the turbidity of the culture water. Oysters stage reduced ammonium concentrations and also the turbidity, beyond had kept low levels of nitrite concentrations in the water, while macroalgae stage did not interfered with ammonium, nitrite, nitrate and turbidity levels. With exception of phosphate, witch practically did not varied throughout the experimental period all the evaluated parameters at all water residence tested times were efficiently reduced by the integrated system. Shrimps presented an excellent development and survival mainly with 72 hours of water residence in the system, and the oysters practically kept its initial biomass. Although macroalgae did not showed a good development and significantly not modify the nutrients levels of the water, they were capable to accumulate nitrogen in the protein form and to increase their absorption capacity when cultivated with nutrients limitation. The results suggest that the establishment of aquaculture integrated systems can be a viable vii alternative for aquafarmers, since it is possible to minimize the environment impacts, provide the costs reduction without water pumping and increase the profits by the production diversification.